Analysis of Determining Service Center Systems towards the Development of The Eastern Part of Medan City - Sinar, T. Ricky Hafidsyah; Milanie, Feby; Nuraini, Cut; Abdiyanto, Abdiyanto; Azhari, Ihsan (International Journal Papier Advance and Scientific Review, 2023)
The issues in the research area include a high concentration of built-up residential areas with the potential for slums and warehousing activities dominating trade and service areas or residential areas, leading to congestion. This requires attention, considering that the Eastern Part of Medan City has a high built-up area, necessitating the provision of affordable infrastructure and basic services for both newcomers and existing residents in the city. Several development theories and concepts can assist in determining and conceptualizing development in the research area. The study focuses on examining the Sub-Central Service System of the City as a center serving sub-urban areas. Various methods are used in determining service centers, including the scalogram method, Marshall's centrality index, and rank-size rule, which will ultimately provide recommendations for the central service system. After issuing recommendations from these three analyses, the determination of the existing urban internal structure is conducted using a scoring method to identify the central service location. Calculations from multiple service center analysis methods are scored and summed to obtain a total score. The neighborhood with the smallest score has the highest hierarchy value, and vice versa. It is revealed that the Sub-Central Service System is present in all sub-districts in the Eastern Part of Medan City, meaning each sub-district in each neighborhood already has comprehensive facilities. Consequently, the four sub-districts in the Eastern Part of Medan City have the potential for development as they meet service needs and can be directed to become service centers serving their respective sub-districts.